Cover Image, Volume 92, Issue 3. Issue 3 (March 2017) - Pan, Yang; Yu, Zongxue; Shi, Heng; Chen, Qi; Zeng, Guangyong; Di, Haihui; Ren, Xiaoqing; He, Yi
Abstract : The cover image, by Zongxue Yu et al., is based on the Research Article A novel antifouling and antibacterial surfacefunctionalized PVDF ultrafiltration membrane via binding Ag/SiO2 nanocomposites, DOI:10.1002/jctb.5034 . Abstract : The cover image, by Zongxue Yu et al., is based on the Research Article A novel antifouling and antibacterial surfacefunctionalized PVDF ultrafiltration membrane via binding Ag/SiO2 nanocomposites, DOI:10.1002/jctb.5034 .